AI in the sustainability of social economy - Belchior-Rocha, H.; Justino, E.; Yener, S. (Economic sustainability potentiated by artificial intelligence, 2025)
Social economy represents a vital sector that prioritizes social and environmental objectives over profit maximization. This sector includes a diverse organization such as cooperatives, mutual benefit societies, associations, and foundations. These entities operate based on principles of democratic governance, reinvestment of profits for social purposes, and autonomy from public authorities. In recent years, the integration of artificial intelligence (AI) into various sectors has shown immense potential to drive efficiency, innovation, and sustainability. The social economy is no exception. AI can provide powerful tools to enhance the effectiveness and impact of social economy initiatives, helping these organizations to better achieve their missions. This chapter explores the intersection of social economy and AI, examining how AI can address the challenges faced by social economy organizations and contribute to sustainable development.